The return of consciousness - Elton, A. Hall (Видавництво НТУ «ДП», 2020)
Consciousness persists in being recognized. Despite a century of efforts to ignore it and even declare it an illusion, it is back, demanding to be understood as part of the universe. Science, led by physics, has had a spectacular career in the last four centuries, resulting in profound theories supported by massive evidence and displayed in technology that has revolutionized our world. Quantum theory, the discovery of DNA, and advances in materials science are all stunning. But science has been missing something: consciousness.
Keywords: філософія свідомості; свідомість